Slaughter weight and carcass of male New Zealand White rabbits after rationing with koro bean (Mucuna pruriens var. utilis) - URIP SANTOSO; SUTARNO SUTARNO (Smujo International, 2009)
Abstract. Santoso U, Sutarno. 2009. Slaughter weight and carcass of male New Zealand White rabbits after rationing with koro bean (Mucuna pruriens var. utilis). Nusantara Bioscience 1: 117-122. The objectives of the research were to know the effects of koro bean (Mucuna pruriens var. utilis) present on slaughter weight and carcass of rabbits and to know the optimum dosage that resulted in the best slaughter weight and carcass. The research used Randomized Block Design whereas 25 heads of six weeks old rabbits with 450-1270 g of body weight were divided into five groups according to the body weight. Each group was treated with different treatment. The treatment was unpresent of M. pruriens as a control (R0) and various percentage of M. pruriens as much as 21.5%, in the ration with treatment as follows: R1 (raw), R2 (heating), R3 (boiling), and R4 (fermentation). The parameters observed were slaughter weight, carcass weight, meat weight, bone weight, and adipose tissue weight. The data analyzed by analysis of variance (ANOVA) followed with Duncan's Multiple Range Test (DMRT). The presence of  processed M. pruriens could increase production of slaughter weight better than the presence of unprocessed M. pruriens. The additional of 21.5% of fermented M. pruriens resulted in the best production of slaughter weight and carcass of rabbits.